Ode to hip-hop : 50 albums that define 50 years of trailblazing music - Fitzgerald, Kiana (Running Press, 2023)
"From underground roots to mainstream popularity, hip-hop's influence on music and entertainment around the world has been nothing short of extraordinary. Ode to Hip-Hop chronicles the journey with profiles of fifty albums that have defined, expanded, and ultimately transformed the genre into what it is today. From 2 Live Crew's groundbreaking As Nasty As They Wanna Be in 1989 to Cardi B's similarly provocative Invasion of Privacy almost thirty years later, and more, Ode to Hip-Hop covers hip-hop from coast to coast. Organized by decade and with sidebars on fashion, mixtapes, and key players throughout, the result is a comprehensive homage to hip-hop, published just in time for the fiftieth anniversary"--